Biomechanical analysis using finite element analysis of orbital floor fractures reproduced in a realistic experimental environment with an anatomical model - Yi, Changryul Claud; Kim, Jaehoon; Jung, Jaebong; Jo, Deoksang; Kim, Ji Hoon (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: In this study, we attempted to demonstrate the actual process of orbital floor fracture visually and computationally in anatomically reconstructed structures and to investigate them using finite element analysis.Methods: A finite element model of the skull and cervical vertebrae was reconstructed from computed tomography data, and an eyeball surrounded by extraocular adipose was modeled in the orbital cavity. Three-dimensional volume mesh was generated using 173,894 of the 4-node hexahedral solid elements.Results: For the cases where the impactor hit the infraorbital foramen, buckling occurred at the orbital bone as a result of the compressive force, and the von Mises stress exceeded 150 MPa. The range of stress components included inferior orbital rim and orbital floor. For the cases where the impactor hit the eyeball first, the orbital bone experienced less stress and the range of stress components limited in orbital floor. The critical speeds for blowout fracture were 4 m/s and 6 m/s for buckling and hydraulic mechanism.Conclusion: Each mechanism has its own fracture inducing energy and its transmission process, type of force causing the fracture, and fracture pattern. It is possible to determine the mechanism of the fracture based on whether an orbital rim fracture is present.